3-6+1=-2x-5+5x

Simple and best practice solution for 3-6+1=-2x-5+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-6+1=-2x-5+5x equation:


Simplifying
3 + -6 + 1 = -2x + -5 + 5x

Combine like terms: 3 + -6 = -3
-3 + 1 = -2x + -5 + 5x

Combine like terms: -3 + 1 = -2
-2 = -2x + -5 + 5x

Reorder the terms:
-2 = -5 + -2x + 5x

Combine like terms: -2x + 5x = 3x
-2 = -5 + 3x

Solving
-2 = -5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-2 + -3x = -5 + 3x + -3x

Combine like terms: 3x + -3x = 0
-2 + -3x = -5 + 0
-2 + -3x = -5

Add '2' to each side of the equation.
-2 + 2 + -3x = -5 + 2

Combine like terms: -2 + 2 = 0
0 + -3x = -5 + 2
-3x = -5 + 2

Combine like terms: -5 + 2 = -3
-3x = -3

Divide each side by '-3'.
x = 1

Simplifying
x = 1

See similar equations:

| 4x+1=9x-7 | | -7-n=-17 | | 5t+16=8t-2 | | 2x+3x+2=10 | | -5(2f+4)=-10 | | .33(21-3a)=6-a | | 5x-6=14-3x | | 15+3x=25 | | 5(f-4)=0 | | 6x+9=-4x-1 | | 5(11w+1)= | | 10+9x=181 | | 10(s-4)=-113 | | -78=7+5n | | -76=2+6a | | slope=1/5:(2,-6) | | (6x+10)(x+2)= | | 2x^3+2x^2-8x-12=0 | | -7x+5=7 | | -2lg(x)+3lg(x^2)=lg(27x) | | u+1.54=5.55 | | n-3/4=1/2 | | 20=3y+4y+6 | | 2(5)y+y=10 | | 12.5=5x+2.25 | | x+3cos(x)=0 | | 10=w+4w | | -2ln(x)+3ln(x^2)=ln(27x) | | 22+3x=1.5x+57 | | 14u-9u=20 | | 5a^2+5a-30=0 | | 11.5+0.9(X)=24.1 |

Equations solver categories